1984
DOI: 10.1073/pnas.81.5.1549
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of calcium channel blockers with non-neuronal benzodiazepine binding sites.

Abstract: The ability of calcium channel blockers to displace the binding of benzodiazepine ligands was investigated in rat heart, kidney, and brain. The dihydropyridine calcium channel blockers nifedipine and nitrendipine displaced the Other calcium channel blockers-i.e., verapamil and diltiazem-were inactive at both sites. Thus, nonneuronal benzodiazepines bind to a class of sites that also binds dihydropyridines. This implies a role for benzodiazepines in the mediation of calcium-dependent phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 26 publications
3
19
0
1
Order By: Relevance
“…This binding site may be involved in the control of calcium channels [25]. It is known that peripherally acting BZDs inhibit plasma membrane cal cium influx at micromolar concentrations [26,27], Taft and De Lorenzo [27] suggested the existence of the dis tinct 'micromolar' binding site for peripherally acting BZDs, connected with the plasma membrane and regulat ing voltage-sensitive calcium channels. On the other hand, the 'peripheral' BZDs may interact with dihydropy ridine binding sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This binding site may be involved in the control of calcium channels [25]. It is known that peripherally acting BZDs inhibit plasma membrane cal cium influx at micromolar concentrations [26,27], Taft and De Lorenzo [27] suggested the existence of the dis tinct 'micromolar' binding site for peripherally acting BZDs, connected with the plasma membrane and regulat ing voltage-sensitive calcium channels. On the other hand, the 'peripheral' BZDs may interact with dihydropy ridine binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the 'peripheral' BZDs may interact with dihydropy ridine binding sites. Cantor et al [26] have shown that nifedipine, a dihydropyridine calcium channel blocker, displaced the tritiated Ro 5-4864 from the membranes of the heart, kidney and brain. Also, the existence of an endogenous protein, which modifies both 'peripheral' BZDs and dihydropyridine calcium channel antagonist binding sites, has been postulated [28],…”
Section: Discussionmentioning
confidence: 99%
“…When given alone, calcium channel antagonists did not produce general anaesthesia, even at very high doses . Micromolar concentrations of benzodiazepines inhibited [3H]-nitrendipine binding (Bender & Hertz, 1985), and micromolar concentrations of calcium channel antagonists displaced binding at the peripheral benzodiazepine receptor (Cantor et al, 1984). As the concentrations required to produce these effects were well in excess of the Kd values for other receptor ligands, a nonspecific effect is the most likely explanation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the site of action of Ro5-4864 remains unclear, there is speculation that its pharmacologic actions may be mediated at the GABA-BDZ receptor complex in the CNS [24,25]. Interaction between Ca++-channel blockers (e.g., nifedipine, nitren dipine) and Ro5-4864 has recently been dem onstrated in brain and other peripheral tis sues [26], and some recent studies have also ascribed several pharmacologic actions of Ro5-4864 to Ca++ antagonism [27][28][29].…”
Section: Discussionmentioning
confidence: 99%